Comments on "Frictional pressure drop correlation for two-phase flows in mini and micro single-channels". (December 2019) - Awad, M.M.
Highlights: These comments are increasing the awareness among the journal readers. Comments are presented in particular on the paper by Li and Hibiki (2017). The two-phase frictional pressure drop equation in homogenous flow model is corrected. The two-phase mixture density ( ρtp ) equation is incorrect. Abstract: The purpose of this discussion is to pay the attention among International Journal of Multiphase Flow readers. Comments are presented on the study by Li and Hibiki (2017) where the researchers presented correlation of frictional pressure drop for two-phase flows in micro and mini single-channels. In this discussion, the two-phase frictional pressure drop equation in homogenous flow model is corrected. In addition, a look on the two-phase mixture density ( ρtp ) equation is presented. From the current analysis, the newcomers to the field of two-phase flow should avoid this wrong definition of the two-phase density ( ρtp ).